(untitled) (Journal of Hama University, 2020)
Ibrahim Nagy is considered one of the pioneers of modernists and flags of contemporary Arab poetry, and through the contract between the constellation of Egyptian renewed poets. So we saw that part of his poerty should be illuminated. This research deals with the phenomenon of deletion in the poetry of Ibrahim Naji, who was known for his compassion and magnificence of his words, and deletion is one of the factors that achieve textual cohesion, and we have indicated to the concept of deletion and its types, including: nominal deletion, actual deletion, bulk deletion, conditions for deletion, the importance of evidence in deletion, and its role in the coherence and consistency of the poetic text, and we undertook an application study on the poem of the " Memorial Day " , Clarified by the previous types of deletion; Let’s get to the effect of this element on his poetry .